Fitoplankton sebagai Bioindikator Saprobitas Perairan di Situ Bulakan Kota Tangerang - Sinta Ramadhania Putri Maresi; Priyanti Priyanti; Etyn Yunita (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
Industry, homes activites, and aquaculture around situ or lake could contaminate and affect the water quality. This study aimed to determine the diversity of phytoplankton and water pollution level in Situ Bulakan Kota Tangerang based on saprobite index. The research was conducted on December 2014 until March 2015 at Situ Bulakan Kota Tangerang. Observations were made based on 4 points sampling with three repetitions for one day that could represented existing condition. Sampling sites in this study were at inlet flow, middle, outlet, and alleged utilized areas such as floating fish net. The result showed 26 species of phytoplankton from four classes, namely 9 species of Cyanophyceae, 4 species of Bacillariophyceae, 11 species of Chlorophyceae, and 2 species of Euglenophyceae with moderate diversity index (H' = 1.77─2.05). Monoraphidium sp. was a species dominated in Situ Bulakan Kota Tangerang which was found 215 individuals. So it can be said as saprobite bioindicator. Saprobite index in Situ Bulakan Kota Tangerang showed moderate to severe contaminated with α-mesosaprobic (0.14).